Role of Attachment and Family Functioning in Problematic Smartphone Use in Young Adults. (February 2022) - Jimeno, M. V.; Ricarte, J. J.; Toledano, A.; Mangialavori, S.; Cacioppo, M.; Ros, L.
Overuse of the smartphone causes negative consequences on the health and behavior of younger people. It is necessary to know which factors can determine the problematic use of the smartphone. The aim of the present study was to explore the relationship between problematic smartphone use, attachment styles, and perceived family functioning in young adults. Three hundred and thirteen Spanish young adults took part in the study (255 women, 58 men) and completed the following instruments: the Smartphone Addiction Scale (SAS), the Relationship Questionnaire (RQ), the Parental Bonding Instrument (PBI), and the Family Adaptability and Cohesion Evaluation Scale (FACES IV). The results of the path analyses show that the cohesion and enmeshed functioning variables were the best predictors of problematic smartphone use. The preoccupied attachment scale was the only one whose score also showed indirect effects on problematic smartphone use through the variable of enmeshed family functioning.